Structural properties of beds packed with agro-industrial solid by-products applicable for solid-state fermentation: Experimental data and effects on process performance - Casciatori, Fernanda Perpetua [UNESP]; Laurentino, Carmem Lucia [UNESP]; Taboga, Sebastiao Roberto [UNESP]; Casciatori, Priscila Aparecida [UNESP]; Thomeo, Joao Claudio [UNESP] (Elsevier B.V., 2014)
The knowledge of structural properties of beds packed with particles from agro-industrial solid wastes is important for modeling and simulation of heat and mass transfer in solid-state fermentation (SSF) in packed-bed bioreactors. This paper addresses the experimental determination of particle and bulk densities (rho(part) and rho(bulk)) and porosities (epsilon) of beds packed with sugar cane bagasse (SCB), wheat bran (WB) and orange pulp and peel (OPP) and with mixtures of them. The effects of moisture content (MC) and packing technique on structural properties were evaluated. Microscopic analysis of cell-size was performed and the porosity along the fermentation was determined, as well as the endoglucanase yields for different proportions of a medium composed by SCB/WB. Results showed that MC affects significantly rho(part), rho(bulk) and epsilon. For OPP and WB, epsilon ranged from 0.4 to 0.7, depending on MC, and for SCB from 0.7 to 0.9, depending on MC and packing technique. For the composed media SCB:OPP:WB (1:2:2, weight) and SCB:WB (7:3), epsilon values were similar to the ones obtained for SCB. The growth of the fungi Myceliophthora thermophila I-1D3b and Trichoderma reesei QM9414 did not affect epsilon of the medium composed by SCB:WB. A comprehensive discussion on how the structural properties of solid matrices affect the performance of SSF processes was done, considering both operational aspects and bioproducts yields. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Agro-industrial by-products; Enzyme production; Packed-beds; Physical properties